2021
DOI: 10.1038/s41420-021-00444-w
|View full text |Cite
|
Sign up to set email alerts
|

Loss of QKI in macrophage aggravates inflammatory bowel disease through amplified ROS signaling and microbiota disproportion

Abstract: Inflammatory bowel disease (IBD) is a refractory chronic inflammatory illness of the gastrointestinal (GI) tract. Macrophage exerts an important role in IBD development. QKI, as an RNA binding protein, was related with inflammatory responses in bacterial infections by regulating the polarization of macrophages. Therefore, we suspected that QKI-regulated macrophages have the potential to play a certain role in IBD and the underlying mechanism. Our results demonstrated that the mice with macrophage-specific dele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…An important foam cell marker, Scavenger receptor A, was found to be directly targeted and repressed by QKI during monocyte differentiation (Wang et al, 2015). In addition, functions for QKI have also been implicated in mature macrophages (L. W. Wang, Zhai, et al, 2021), re-enforcing the notion that QKI participates in the differentiation and maintenance of macrophage phenotypes.…”
Section: Qki and Differentiation Of Monocytesmentioning
confidence: 93%
“…An important foam cell marker, Scavenger receptor A, was found to be directly targeted and repressed by QKI during monocyte differentiation (Wang et al, 2015). In addition, functions for QKI have also been implicated in mature macrophages (L. W. Wang, Zhai, et al, 2021), re-enforcing the notion that QKI participates in the differentiation and maintenance of macrophage phenotypes.…”
Section: Qki and Differentiation Of Monocytesmentioning
confidence: 93%
“…These physiological factors are responsible for the low survival rate and limited intestinal colonization of probiotics. , More importantly, pathological conditions in IBD can also seriously impede the colonization of probiotics. For example, there is a high concentration of reactive oxygen species (ROS) in the pathological microenvironment. , ROS have a strong oxidation effect on lipids and proteins on the surface of probiotics, which can cause major damage to the cell wall of bacteria and lead to their inactivation. In addition, bacteria usually colonize in the mucus layer, which is essential for maintaining the intestinal mucosal barrier under physiological conditions. , However, because the mucus layer in the inflammatory site is often exhausted and the intestinal mucosal barrier badly damaged, , oral probiotics may pass through the intestinal barrier into the bloodstream, causing dangerous side effects such as bacterial translocation. , These problems can prevent probiotics from reaching the intestinal tract in a sufficient amount of active form to colonize the intestinal tract and to have good therapeutic effects. As such, the ability to resist the adverse physiological and pathological conditions in the gastrointestinal tract and the ability to adhere to intestinal mucosa are important factors for the colonization of probiotics in the intestine.…”
mentioning
confidence: 99%
“…Macrophages are a double-edged sword, as their excessive activation can lead to inflammatory activation mediated by microbiota through the secretion of LPS [ 31 ]. Studies have shown that changes in gut microbiota mediated by macrophage dysfunction result in higher susceptibility to IBD [ 32 , 33 ]. The components of the local tissue microenvironment, such as cytokines, microbiota, microbial products, and other immune and stromal cells, more or less determine the macrophage response [ 28 ].…”
Section: Gut Microbiota Participate In the Progression Of Ibdmentioning
confidence: 99%